Lutter contre le dopage par une dépénalisation reconstructive du sportif coupable : les enjeux et les ambiguïtés du projet Windop? - Veuthey, A.; Jaccoud, C.; Malatesta, D.; Hafner, Y. (Movement & Sport Sciences - Science & Motricité, 2016)
The fight against doping shows an increasing trend towards articulating an axis of law, built on sanctions, and an axis of regulation rooted in arbitration and conciliation principles mindful of the notions of athletes` dignity. We illustrate our argument and the ambiguities of this fight through a socio-legal analysis of the first elements of the implementation of the anti-doping pilot project Windop. This project, financially supported by the World Anti-Doping Agency (WADA) and benefitting from the expertise of sociologists and psychologists, has, since 2010, intended to rehabilitate athletes found guilty of doping, through various support measures aimed at recognizing the fault, preventing repetition of an offence and rebuilding a sporting future.